HUMANIZM A EDUKACJA DZIECI HENRYKA VIII - Smoluk, Marek (In Gremium. Studies in History, Culture and Politics, 2008)
HUMANISM AND ROYAL EDUCATION OF HENRY VIII’ CHILDREN S u m m a r y With the advent of humanism in England, native scholars were increasingly aware that if they were to be successful, the two distinct fields in which they had to inculcate humanistic ideas were the king’s court and the universities. In order gain authorisation to practise in the lecture rooms and to encourage their students to take an interest in the study of both Latin and Greek, and expose their listeners to uncorrupted and original classical texts, English humanists had to obtain royal approval of this new approach to teaching. In order to persuade the monarch around to their way of thinking, understanding the world, interpreting the Bible and teaching future generations, they had to prove that their capabilities and intellectual capacity outstripped those of their competitors - the old-fashioned lecturers from medieval monasteries. The prime sensitive area in which humanists could achieve their goals and make their influence felt was the education of the sovereign’s children. The principal aim of this paper is to offer an insight into the detail of educating the king’s offspring in Tudor times. There is no dispute amongst most historians that the kind of education a prince or princess underwent and the religion instruction they received in their youth, are the two most determining factors which influence the future king’s or queen’s reign. Thus this paper allows the reader to learn of certain nuances affecting the royal Tudor education provided by the English scholars to Henry VIII’ children – viz. the Princesses Mary and Elizabeth as well as Prince Edward.